Molecular, Biochemical and Histological Assessment in Paraquat Induced Neurotoxicity: Restoring Role of Nano-curcumin in an Experimental Study - Mojdeh Mohammadi; Seyed Sina Tajedini; Zohre Sadeghian; Sara Soleimani Asl; Nejat Kheiripour; Mohammadmahdi Sabahi; Akram Ranjbar (Acta Neurologica Taiwanica)
Background: Paraquat (PQ) is known to cause damage to various organs, including the brain. Although curcumin have anti-inflammatory and anti-oxidant properties, it is not yet clear how they relate to PQ-induced neurotoxicity. This study’s objective was to compare the effects of curcumin and nanocurcumin on PQ-induced neurotoxicity in male rats. Methods: 36 rats were randomly divided into 6 groups. control subjects and animals poisoned with PQ that received treatment with or without curcumin and nano-curcumin for 7 days. The brain tissues were collected at the end of this period. Total antioxidant capacity (TAC), lipid peroxidation (LPO), and total thiol groups (TTG) were assessed by using spectrophotometry. Moreover, the histopathology of brain and antioxidant gene expression were assessed by biochemical and reverse transcriptase polymerase chain reaction (RT-PCR) analysis. Results: Curcumin and nanocurcumin therapy alleviated the PQ-triggered oxidative stress in brain tissue by raising the levels of anti-oxidant biomarkers like TAC and TTG, up-regulating the expression of Nrf2, HO-1, and NQO-1, reducing the levels of oxidative stress indices like LPO, and down- regulating the expression of Keap-1 in brain tissue. Conclusions: Treatment with curcumin and nano-curcumin improves brain function in PQ toxicity and nanocurcumin was more advantageous than ordinary curcumin.